Hamleś Skolimowskiego jako parodia - Hendrykowski, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2014)
Hamleś is a brilliant etude made in 1960 by young film-maker Jerzy Skolimowski during his studies in famous Film School in Łódź. In ballad form this mysterious and dark story tells about lost hopes of freedom and strange situation of Polish intelligentsia of the late 1950s in connection with characters of Shakespeare’s tragedy. Skolimowski’s parody has typical for this artistic obsessive-compulsive dimension (Don Fredericksen’s term). Skolimowski took the title and protagonists from the classic drama and transmitted the main subject in a way that is much darker and ironic than the original.